Art and Disability: Intersecting Identities Among Young Artists with Disabilities - Sulewski, Jennifer Sullivan; Boeltzig, Heike; Hasnain, Rooshey (Disability Studies Quarterly, 2012)
Disability arts in the United Kingdom and disability culture in the United States play important roles in expressing a positive disability identity. This paper reports on expressions about identity, in both artwork and reflective words, of 47 young artists with disabilities who were finalists in the VSA arts / Volkswagen arts competition between 2002 and 2005. As part of an evaluation of this program, we reviewed the artists' application essays and artwork. In doing so, we found a wealth of information on their perceptions of what it means to be a person with a disability and an artist, and how these two identities intersect. The findings provide insights into the role of the arts in identity formation for young people with disabilities, and point to the potential for future research on how arts and disability interact. Keywords affirmative model of disability, impairment, art, artists, culture, identity